The Cell Surface GRP78 Facilitates the Invasion of Hepatocellular Carcinoma Cells. (8th December 2013) - Zhang, Xiu-Xiu; Li, Hong-Dan; Zhao, Song; Zhao, Liang; Song, Hui-Juan; Wang, Guan; Guo, Qing-Jun; Luan, Zhi-Dong; Su, Rong-Jian
Abstract : Invasion is a major characteristic of hepatocellular carcinoma and one of the main causes of refractory to treatment. We have previously reported that GRP78 promotes the invasion of hepatocellular carcinoma although the mechanism underlying this change remains uncertain. In this paper, we explored the role of the cell surface GRP78 in the regulation of cancer cell invasion in hepatocellular carcinoma cells. We found that neutralization of the endogenous cell surface GRP78 with the anti-GRP78 antibody inhibited the adhesion and invasion in hepatocellular carcinoma cell lines Mahlavu and SMMC7721. However, forced expression of the cell surface GRP78 facilitated the adhesion and invasion in SMMC7721. We further demonstrated that inhibition of the endogenous cell surface GRP78 specifically inhibited the secretion and activity of MMP-2 but did not affect the secretion and activity of MMP-9. We also found that inhibition of the cell surface GRP78 increased E-Cadherin expression and decreased N-Cadherin level. On the contrary, forced expression of the cell surface GRP78 increased N-Cadherin expression and decreased E-Cadherin level, suggesting that the cell surface GRP78 plays critical role in the regulation of EMT process. These findings suggest that the cell surface GRP78 plays a stimulatory role in the invasion process and may be a potential anti-invasion target for the treatment of hepatocellular carcinoma.